(3JHjjf GdMbGFb TQM cfR GdObGFbs - (3aNQ GdOjf CHh eMeO YKeGf Hf Ydj Hf eMLf GdRjdYj, YKeGf GdRjdYj,J (B743 (3g` s ((3eMeO Hf Ydi GdZRhdi GdMfai s)
(3ChdgG (B:s
(3cJGH GdWdGb bGd QMeg Gddg gh QaY GdbjO GdKGHJ TQYG HGdfcGM s
(3BNQgG (B:s
(3hddg GdMeO hGdefI Je GdLRA GdKGfi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B373s
Keywords: (3Gdabg GdMfajs